Filling a Representation Gap? How Populist and Mainstream Parties Address Muslim Immigration and the Role of Islam. Issue 4 (2nd October 2019) - Kortmann, Matthias; Stecker, Christian; Weiß, Tobias
ABSTRACT: This paper asks whether Germany's main right-wing Populist Party, the AfD, filled a representation gap on the issue of Muslim immigration and integration and the role of Islam. We shed light on this question by analysing more than 575 manifestos from all 116 elections on the state and federal level between 1990 and 2017. A quantitative text analysis reveals that all parties increased their attention towards the topic in the recent years, while the AfD is most attentive. A qualitative framing analysis shows that the AfD did not bring any new ideas, problems or solutions to the debate but stands out from mainstream parties by drawing an exclusively negative picture of Muslims and Islam clearly exaggerating the differentiated – yet still critical – views represented by CDU and CSU. The results suggest a minor representation gap in the East of Germany, potentially contributing to the AfD's success.